2021
DOI: 10.1177/09564624211046516
|View full text |Cite
|
Sign up to set email alerts
|

Undetected anogenital sexually transmitted infections among young adults living with HIV and receiving antiretroviral therapy: Implications for HIV treatment as prevention

Abstract: Undetected sexually transmitted infections (STIs) pose health threats to people living with HIV and when combined with uncontrolled HIV can amplify HIV transmission. The current study screened 174 self-identified men under age 36 living with HIV and receiving antiretroviral therapy (ART) for urethral and rectal incident chlamydia and gonorrhea infections. Participants were also screened for biomarkers indicating alcohol and other drug use, subclinical genital inflammation, and HIV viral load. ART adherence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
1
Order By: Relevance
“…This finding explains why this study's monitoring/evaluation of HIV/AIDs prevention programmes suggested a high extent. The findings, however, contradict other studies that documented that the rising frequency of sexually transmitted illnesses, especially HIV/AIDS, demonstrates that previous attempts to combat the pandemic have been insufficient, even with antiretroviral therapy (Kalichman, Eaton, and Kalichman 2021;Mosha et al 2022;Jing et al 2022;Thitipatarakorn et al 2022). The disparity in results might be related to variations in the factors included in the investigations.…”
Section: Discussion Of Findingscontrasting
confidence: 85%
“…This finding explains why this study's monitoring/evaluation of HIV/AIDs prevention programmes suggested a high extent. The findings, however, contradict other studies that documented that the rising frequency of sexually transmitted illnesses, especially HIV/AIDS, demonstrates that previous attempts to combat the pandemic have been insufficient, even with antiretroviral therapy (Kalichman, Eaton, and Kalichman 2021;Mosha et al 2022;Jing et al 2022;Thitipatarakorn et al 2022). The disparity in results might be related to variations in the factors included in the investigations.…”
Section: Discussion Of Findingscontrasting
confidence: 85%